The impact of US export controls on Korean semiconductor exports - Hanhin Kim; Jaehan Cho (KDI Journal of Economic Policy, 2024)
This study empirically investigates the impact of recent US export controls on China on South Korea's semiconductor exports. We analyze South Korean export data to shed light on the repercussions of US export restrictions on a third country. Our findings reveal a significant decline in Korean semiconductor exports following the October 2022 imposition of US controls. This decline was most pronounced in the memory, discrete devices, and discrete device components subsectors of the semiconductor industry. In addition, we observed a decrease in unit prices, especially for memory semiconductors, pointing to downward pressure on South Korea's high-value-added semiconductor exports. These results provide some evidence of substantial negative impacts of US export controls on South Korea's semiconductor industry, and particularly with regard to its high-tech products.
Keywords: F13; F14; F51; 330; US Export Controls; South Korean Exports; Semiconductors; Export Control Classification Numbers(ECCNs); Gravity Equation